Leading order determination of the gluon polarisation from DIS events with high-$p_T$ hadron pairs - COMPASS collaboration (216 authors); Bordalo, P.; Franco, C.; Nunes, A.S.; Quaresma, M.; Quintans, C.; Ramos, S.; Silva, L.; Stolarski, M. (My University, 2013)
We present a determination of the gluon polarisation Delta g/g in the nucleon, based on the longitudinal double-spin asymmetry of DIS events with a pair of large transverse-momentum hadrons in the final state. The data were obtained by the COMPASS experiment at CERN using a 160 GeV/c polarised muon beam scattering off a polarised ^6LiD target. The gluon polarisation is evaluated by a Neural Network approach for three intervals of the gluon momentum fraction x_g covering the range 0.04 < x_g < 0.27. The values obtained at leading order in QCD do not show any significant dependence on x_g. Their average is Delta g/g = 0.125 +/- 0.060 (stat.) +/- 0.063 (syst.) at x_g=0.09 and a scale of mu^2 = 3 (GeV/c)^2.